2022
DOI: 10.1007/s12028-022-01510-6
|View full text |Cite
|
Sign up to set email alerts
|

Modern Learning from Big Data in Critical Care: Primum Non Nocere

Abstract: Large and complex data sets are increasingly available for research in critical care. To analyze these data, researchers use techniques commonly referred to as statistical learning or machine learning (ML). The latter is known for large successes in the field of diagnostics, for example, by identification of radiological anomalies. In other research areas, such as clustering and prediction studies, there is more discussion regarding the benefit and efficiency of ML techniques compared with statistical learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Some experts in statistical modeling have suggested that machine learning has no advantage over standard regression modeling 54 . Future research will be necessary to determine whether machine learning techniques have the potential to mitigate existing pitfalls in statistical modeling, including biases arising from withdrawal of life-sustaining treatments and the associated self-fulfilling prophecy 55 …”
Section: How Should We Go About Neuroprognostication?mentioning
confidence: 99%
“…Some experts in statistical modeling have suggested that machine learning has no advantage over standard regression modeling 54 . Future research will be necessary to determine whether machine learning techniques have the potential to mitigate existing pitfalls in statistical modeling, including biases arising from withdrawal of life-sustaining treatments and the associated self-fulfilling prophecy 55 …”
Section: How Should We Go About Neuroprognostication?mentioning
confidence: 99%
“…Clustering algorithms commonly are performed in a static way with baseline data and/or outcome data. They are useful to answer descriptive questions (10,11). In the early attempts, unsupervised clustering analysis algorithms were used on clinical laboratory indexes and demographic data characteristics of patients with heart failure to make homogeneous inductive groups (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners often struggle when reviewing the ever-expanding panoply of publications applying machine learning techniques to data analysis, not knowing how to critically review the methodological machinations behind the curtain of these algorithms. Gravesteijn and colleagues [20] provide a valuable review of machine learning's strengths and pitfalls, including the use of clustering to find endotypes (as proposed in the articles cited above) and the critical need for skepticism and validation of findings from machine learning studies. In addition, we must remember that an ethical and equity-minded perspective must be applied when collecting and implementing data-driven decision making in medicine [21].…”
mentioning
confidence: 99%